El proceso de enseñanza de la composición escrita adaptado a la evolución del aprendizaje de la escritura de los estudiantes - García García, Mercedes; Albarrán Santiago, Manuel (Didáctica. Lengua y Literatura, 2010)
Written composition is an essential skill that, in the present education systems, must be achieved by each person at the end of their required schooling. Every school is responsible for providing students with writing skills, and this has been so since some decades ago. This paper aims at offering, under an integral teaching focus, the use of cognitive operations related to written composition, by recognizing the evolution of students’ learning of writing. Consequently, five stages are proposed: I) Previous conscious perception, II) Grammar acquisition and written presentation, III), Acquisition of text typology, IV) Acquisition of the written presentation, and V) Acquisition of content and text length. Finally, it is suggested that students are able to write quality papers, only if all of us consider teaching from a diagnostic-prescriptive-evaluative process view, such a way teaching processes may begin and control the acquisition of skills for students so that they can take their own decisions about which teaching strategies they will use in each case.